A qualidade das práticas educativas em uma creche do município de Santo André/SP - Silva, José Carlos da (2018)
This intervation-research has as an object the quality of educational practices in nursery. Has as a general objective analize the quality of educational practices of a nursery that attend babies from 0 to 2 years old, located in a nursery in the municipality of Santo André (SP), considering, mainly for three aspects: partnership with the family, continuing education of teachers, and the organizationof spaces and time in the day care. As an especific objective outlined: understand how two Child Development Aids (CDA), one intern and the teacher developed their work with the babies and what are their conceptions of nursery, child and childhood. We seek for answer the following questions: as na CDA, the intern and the teacher understand the role of the nursery? What conceptions of children and childhood permeate the educational practices of these professional? They consider the nursery as a right for the child or the working mom? The metodology is qualitative and the instrument of data collection is the observation of the practice, discussion in conversation wheels and reflections together with a teacher, two child assistants and na intern, in the room of Work Organization (WO) meeting, beyond the analyses of the documents of Education. As theoretical reference we refer to the following authors: Kramer (1992), Campos (2011), Rossetti-Ferreira (2002), Oliveira (2011), Craidy (2001), Freire (1996), Kuhlmann Júnior (1998, 2010) and Zabalza (1998). We found with this research that the teacher and other professionals present divergences of conceptions of children, which hinder the cohesion of the work group in the conduct of the same procedures for the different situations and moments of care and education. Given the data, it was possible to identify the need for incentive, optimization of times and spaces, and continuous training offered through public policies of the municipality; as well as formations in the unit itself in which all segments can discuss and reflect on aspects of the pedagogical routine.